Fear of floating and fear of pegging: An empirical anaysis of de facto exchange rate regimes in developing countries - Jizhong Zhou; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper uses a panel probit model with simultaneous equations to explain the joint determination of de facto and de jure exchange rate regimes in developing countries since 1980. We also derive an ordered-choice panel probit model to explain the causes of discrepancies between the two regime choices. Both models are estimated using simulation-based maximum likelihood methodsl. The results of the simultaneous equations model suggest that the two regime choices are dependent of each other and exhibit considerable state dependence. The ordered probit model provides evidence that regime discrepancies reflect an error-correction mechanism, and the discrepancies are persistent over time.
Keywords: F33; F41; C35; 330; de facto exchange rate regimes; developing countries; simultaneous equations model; simulated maximum likelihood; Wechselkurssystem; Wechselkurspolitik; Schätzung; Entwicklungsländer